University-industry collaboration: The impact of postdoctoral workstations on labor investment efficiency - Liu, Yiding; Yi, Kefu; Huang, Guanhua (Frontiers in Psychology, 2022)
This paper investigates whether managers use knowledge transferred from university-industry collaboration when making investment decisions on labour. To establish causality, we use a difference-in-difference method based on the staggered establishment of postdoctoral workstations in Chinese firms. We find that postdoctoral workstations enable managers to improve the labour investment efficiency and thus help mitigate over- and under-investment problems in labour. This finding is robust to utilizing the event study approach, placebo test, and entropy balancing. Brain gain and knowledge transfer effects between the universities and industries are two plausible mechanisms. Furthermore, the main effect is more pronounced for firms located closer to prestigious universities, firms are non-state-owned enterprises and human-capital-intensive. Our findings suggest that brain gain into firms does not merely increase or reduce labour investments per se, but rather inspires managers to maintain optimal labour levels through knowledge transfer processes.